IMPLEMENTASI METODE DEMONSTRASI DALAM PERAWATAN JENAZAH PADA PEMBELAJARAN UBUDIYAH - Samsul Arifin; Mohammad Ahyan Yusuf Sya’bani (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2023)
Accuracy in applying methods to learning activities is an important factor in the success of learning activities. The teacher chooses to apply the demonstration learning method to be applied in the hope that all the objectives of carrying out practical learning for organizing corpses can be conveyed optimally and in the right way. This study aims to find out how the implementation of the demonstration method in caring for corpses in ubudiyah learning for class IX MTs Thoriqul Huda Randupadangan Menganti Gresik Village. This research uses a qualitative approach with a case study type. The procedure for collecting data is by observation, structured interviews, and documentation. The data analysis used is reduction, data display and then conclusions are drawn according to the research objectives. The results of this study, that the application of the demonstration method begins with an explanation related to the material to be demonstrated. In the core activities, the teacher describes the demonstration method, especially the material for organizing the funeral, in detail, the students can practice holding the funeral directly. In closing the teaching and learning activities the teacher provides opportunities for students to ask questions that are not yet understood and provide explanations about things that are not understood. The subject matter demonstrated included washing the corpse, shrouding the corpse, praying for the corpse, and burying it.